Using formative research to design context‐specific animal source food and multiple micronutrient powder interventions to improve the consumption of micronutrients by infants and young children in Tanzania, Kenya, Bangladesh and Pakistan. Issue 2 (16th October 2020) - Robert, Rebecca C.; Bartolini, Rosario M.; Creed‐Kanashiro, Hilary M.; Verney Sward, Allison
Abstract: Optimal complementary feeding practices including consumption of multiple micronutrient powders (MNP) are recommended to improve micronutrient intake by infants and young children (IYC) 6–23 months. Formative research was used to design the behaviour change strategy to improve IYC micronutrient intake for the multicountry ENRICH project in rural impoverished areas of Tanzania, Kenya, Bangladesh and Pakistan. Employing a qualitative approach with multiple methods and guided by a social ecological framework, the study was conducted in several phases: data collection in the community, household and health facilities, initial analysis and household trials (HHT). Results found limited use of animal source foods (ASF) for feeding IYC and MNP largely unavailable. Although cost constrained access to ASF, potential more affordable context‐specific ASF options were identified in each setting. Caregivers associated ASF with many positive attributes for IYC, but barriers to feeding them included lack of caregiver time and knowledge of specific preparation techniques, and limited advice from health workers. Feeding practices were identified that used time‐efficient, specific preparations for eggs and other ASF, and demonstrated good initial acceptability and feasibility during HHT. Testing MNP in HHT found good initial feasibility and acceptability and provided an understanding of the facilitators and constraints for preparing, feeding and promoting MNP. In conclusion, formative research led to the design of context‐specific ASF and MNP complementary feeding promotion strategies to improve IYC consumption of micronutrients by identifying the practices, benefits, motivations and alternative actions to overcome the barriers in each setting.